Molecular and physiologic mechanisms of advanced ripening by trunk girdling at early veraison of ‘Summer Black’ grape - Peng, Yanjie; Gu, Xingjia; Zhou, Qi; Huang, Jiao; Liu, Zhong; Zhou, Yong; Zheng, Ying (Frontiers in Plant Science, 2022)
Although the effects of girdling on grape berry development have been widely studied, the underlying mechanisms are poorly understood, especially at the molecular level. This study investigated the effect of trunk girdling on grape (Vitis L.) berry maturation. Girdling was performed on 5-year-old ‘Summer Black’ grapevines at early veraison, and transcriptional and physiologic analyses were performed. Trunk girdling promoted sugar accumulation and color development in berries and accelerated berry ripening by 25 days. Genes related to sucrose cleavage and polysaccharide degradation were upregulated at the transcriptional level, which was associated with increased monosaccharide accumulation and berry softening. Anthocyanin biosynthesis and accumulation were also enhanced by trunk girdling through the upregulation of anthocyanin biosynthesis genes including phenylalanine ammonia-lyase and UDP-glucose:flavonoid 3-O-glucosyltransferase (UFGT). The increased expression of two VvUFGT genes was accompanied by the upregulation of VvMYBA2 under girdling. The upregulation of genes involved in ethylene biosynthesis and hormone (abscisic acid and brassinosteroid) responses and downregulation of genes involved in indoleacetic acid biosynthesis and response may have also promoted berry ripening in the girdling group. A total of 120 differentially expressed transcription factor genes from 29 gene families including MYB, ERF, and MYB-related were identified in the girdling group, which may participate in the regulation of berry development and ripening. These results provide molecular-level insight into the positive effects of trunk girdling on berry development in grapes.